Dynamics of antibody titers and cellular immunity among Japanese healthcare workers during the 6 months after receiving two doses of BNT162b2 mRNA vaccine. Issue 32 (30th July 2022) - Uwamino, Yoshifumi; Kurafuji, Toshinobu; Takato, Kumiko; Sakai, Akiko; Tanabe, Akiko; Noguchi, Masayo; Yatabe, Yoko; Arai, Tomoko; Ohno, Akemi; Tomita, Yukari; Shibata, Ayako; Yokota, Hiromitsu; et al.
Abstract: Background: The antibody titer is known to wane within months after receiving two doses of the Pfizer-BioNTech BNT162b2 mRNA SARS-CoV-2 vaccine. However, knowledge of the cellular immune response dynamics following vaccination is limited. This study to aimed to determine antibody and cellular immune responses following vaccination, and the incidence and determinants of breakthrough infection. Methods: This prospective cohort study a 6-month follow-up period was conducted among Japanese healthcare workers. All participants received two doses of BNT162b2 vaccine. Anti-SARS-CoV-2 antibody titers and T-cell immune responses were measured in serum samples collected at several timepoints before and after vaccination. Results: A total of 608 participants were included in the analysis. Antibody titers were elevated 3 weeks after vaccination and waned over the remainder of the study period. T-cell immune responses showed similar dynamics. Six participants without predisposing medical conditions seroconverted from negative to positive on the IgG assay for nucleocapsid proteins, indicating breakthrough SARS-CoV-2 infection. Five of the six breakthrough infections were asymptomatic. Conclusions: Both humoral and cellular immunity waned within 6 months after BNT162b2 vaccination. The incidence of asymptomatic breakthrough infection within 6 months after vaccination was approximately one percent. UMIN Clinical Trials Registry ID: UMIN000043340.